Identification of watermelon genes involved in the ZYMV interaction through a miRNA bio-informatics analysis and characterization of ATRIP and RBOHB - Margarita Berbati; Maria Bousali; Athanasios Kaldis; Tomas Moravec; Timokratis Karamitros; Andreas Voloudakis (Physiological and Molecular Plant Pathology, 2024)

Silencing of a Nicotiana benthamiana ascorbate oxidase gene reveals its involvement in resistance against cucumber mosaic virus - Reshma Ahmed; Athanasios Kaldis; Andreas Voloudakis (Planta, 2024)
Main conclusion Silencing of an ascorbate oxidase ( AO ) gene in N. benthamiana enhanced disease severity from cucumber mosaic virus (CMV), showing higher accumulation and expansion of the spreading area of CMV. Abstract A Nicotiana benthamiana ascorbate oxidase ( NbAO ) gene was found to be induced upon cucumber mosaic virus (CMV) infection. Virus-induced gene silencing (VIGS) was employed to elucidate the function of AO in N. benthamiana . The tobacco rattle virus (TRV)-mediated VIGS resulted in an efficient silencing of the NbAO gene, i.e., 97.5% and 78.8% in relative quantification as compared to the control groups (TRV::eGFP- and the mock-inoculated plants), respectively. In addition, AO enzymatic activity decreased in the TRV::NtAO-silenced plants as compared to control. TRV::NtAO-mediated NbAO silencing induced a greater reduction in plant height by 15.2% upon CMV infection. CMV titer at 3 dpi was increased in the systemic leaves of NbAO -silenced plants (a 35-fold change difference as compared to the TRV::eGFP-treated group). Interestingly, CMV and TRV titers vary in different parts of systemically infected N. benthamiana leaves. In TRV::eGFP-treated plants, CMV accumulated only at the top half of the leaf, whereas the bottom half of the leaf was “occupied” by TRV. In contrast, in the NbAO -silenced plants, CMV accumulated in both the top and the bottom half of the leaf, suggesting that the silencing of the NbAO gene resulted in the expansion of the spreading area of CMV. Our data suggest that the AO gene might function as a resistant factor against CMV infection in N. benthamiana .

The Citrus yellow mosaic badnavirus ORFI functions as a RNA-silencing suppressor - Tharanath Vadlamudi; Athanasios Kaldis; Venkataramana Sai Gopal Divi; Basavaprabhu L. Patil; Andreas E. Voloudakis (Virus Genes, 2021)

Topical application of double stranded RNA molecules deriving from Sesbania mosaic virus (SeMV) CP and MP genes protects Sesbania plants against SeMV - Naga Charan Konakalla; Athanasios Kaldis; Hema Masarapu; Andreas E. Voloudakis (European Journal of Plant Pathology, 2019)

The histone acetyltransferase GCN5 and the transcriptional coactivator ADA2b affect leaf development and trichome morphogenesis in Arabidopsis - Jenna Kotak; Marina Saisana; Vasilis Gegas; Nikoletta Pechlivani; Athanasios Kaldis; Panagiotis Papoutsoglou; Athanasios Makris; Julia Burns; Ashley L. Kendig; Minnah Sheikh; Cyrus E. Kuschner; Gabrielle Whitney; et al. (Planta, 2018)

Plant insects and mites uptake double-stranded RNA upon its exogenous application on tomato leaves - Anupam Gogoi; Nomi Sarmah; Athanasios Kaldis; Dionysios Perdikis; Andreas Voloudakis (Planta, 2017)

Exogenous application of double-stranded RNA molecules from TMV p126 and CP genes confers resistance against TMV in tobacco - Naga Charan Konakalla; Athanasios Kaldis; Margarita Berbati; Hema Masarapu; Andreas E. Voloudakis (Planta, 2016)

Arabidopsis thaliana transcriptional co-activators ADA2b and SGF29a are implicated in salt stress responses - Athanasios Kaldis; Despoina Tsementzi; Oznur Tanriverdi; Konstantinos E. Vlachonasios (Planta, 2011)

The histone acetyltransferase GCN5 affects the inflorescence meristem and stamen development in Arabidopsis - Ross Cohen; John Schocken; Athanasios Kaldis; Konstantinos E. Vlachonasios; Amy T. Hark; Elizabeth R. McCain (Planta, 2009)

Synergy between the light-induced acute response and the circadian cycle: a new mechanism for the synchronization of the Phaseolus vulgaris clock to light - Athanasios-Dimitrios Kaldis; Anastasia Prombona (Plant Molecular Biology, 2006)

Light and circadian regulation in the expression of LHY and Lhcb genes in Phaseolus vulgaris - Athanasios-Dimitrios Kaldis; Panagiotis Kousidis; Konstantinos Kesanopoulos; Anastasia Prombona (Plant Molecular Biology, 2003)